The Transformation of the State’s Role in Child Protection in Indonesia - Sulistyowati Sulistyowati; Widya Romasindah Aidy; Gusti Bintang Maharaja (International Research of Multidisciplinary Analysis, 2026)
The state’s role in child protection in Indonesia has undergone a fundamental shift over time. Initially, the Indonesian state played only a minimal role, adopting a charitable or philanthropic approach. However, over time—and driven by various pressures from international law as well as domestic needs—the state became the primary guarantor of the fulfillment and protection of children’s rights. This transformation did not occur suddenly but rather through a series of ratifications of international conventions, constitutional amendments, and the establishment of various laws and child protection institutions. This article aims to provide an in-depth analysis of the evolution of child protection law and policy in Indonesia, as well as a theoretical reconstruction of the state’s responsibilities. Additionally, this article examines the implementation of institutional structures and the decentralization of services. The method used is a literature review employing a normative qualitative approach. The findings indicate that although various national indicators—such as the child protection index—continue to improve and public awareness regarding the reporting of violence cases is also increasing, there remain several serious structural barriers. These obstacles include a shortage of professional human resources at the regional level, weak inter-sectoral coordination, and a legal vacuum regarding the criminal liability of parents who neglect their duty to supervise their children. This article recommends strengthening regional capacity by recruiting experts, reforming juvenile criminal law by applying the theory of dual liability, integrating the national information system, and fostering sustainable cross-sectoral collaboration